Evaluation of systemic inflammatory and nutritional indexes in locally advanced gastric cancer treated with adjuvant chemoradiotherapy after D2 dissection - Wang, Shu-Bei; Chen, Jia-Yi; Xu, Cheng; Cao, Wei-Guo; Cai, Rong; Cao, Lu; Cai, Gang (Frontiers in Oncology, 2022)
Background Many studies have shown that the peripheral blood inflammatory index and nutritional index, such as the platelet lymphocyte ratio (PLR), neutrophil lymphocyte ratio (NLR), lymphocyte monocyte ratio (LMR), systemic inflammation response index (SIRI), pan-immune-inflammation value (PIV), systemic immune-inflammation index (SII), and prognostic nutrition index (PNI), are independent prognostic factors for tumors. The present study aimed to investigate the prognostic role of these peripheral blood indexes before treatment in locally advanced gastric cancer (LAGC) treated with adjuvant chemoradiotherapy after D2 dissection. Methods A total of 89 patients with LAGC who underwent D2 gastrectomy and adjuvant chemoradiotherapy at our hospital from 2010–2018 were eligible. Systemic inflammatory indicators before treatment were evaluated. Receiver operating characteristic curve (ROC), Kaplan–Meier analysis, and Cox regression were utilized for prognosis evaluation. Results The median follow-up time was 29.1 (4.1–115.8) months. The overall survival at 3 years (OS) and the disease-free survival (DFS) were 78.9% and 59.1%, respectively. According to the ROC curve for 3-year DFS, the best cut-off values of pre-treatment NLR, PLR, LMR, SII, SIRI, PIV and PNI were 1.7, 109.3, 2.9, 369.2, 0.58, 218.7, and 48, respectively. Multivariate Cox regression analysis showed that NLR was an independent prognostic factor for DFS (HR 2.991, 95%CI 1.085–8.248, P = 0.034). Kaplan-Meier analysis showed that a higher NLR (>1.70) was significantly associated with a poorer OS (3-year OS: 68.8% vs 92.9%, P = 0.045) and DFS (3-year DFS: 47.5% vs 80.9%, P = 0.005). In terms of the free locoregional recurrence rate (LRR), the prognosis of patients with high NLR was also significantly worse than those with low NLR (70.2% vs 96.0%, P = 0.017). Paraaortic lymph nodes were the most common site of LRR (7/14 patients). The seven cases of paraaortic lymph node metastasis occurred in patients with high NLR. Conclusions In our retrospective analysis, we found that pretreatment NLR could serve as a prognostic factor for survival in LAGC treated with adjuvant chemoradiotherapy after D2 dissection, especially for the prediction of LRR and paraaortic lymph node metastasis. Prospective studies are needed to confirm our findings.